2006
DOI: 10.2807/esm.11.06.00631-en
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase of listeriosis in Germany - Epidemiological patterns 2001-2005

Abstract: Listeriosis has been a mandatorily notifiable disease in Germany since January 2001. Clinical cases with isolation of Listeria monocytogenes from sterile specimens or neonates are reported to the Robert Koch-Institut. Listeriosis incidence significantly increased from 0.26 per 100 000 inhabitants (217 cases) in 2001 to 0.62 per 100 000 (519 cases) in 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 0 publications
3
31
0
3
Order By: Relevance
“…5 Countries with surveillance programs have reported rates of infection from 0.6 to 6.2 cases per million, with countries having active surveillance programs reporting the highest incidence. 5,[7][8][9][10][11] The case-fatality rates vary from country to country, but invariably the highest mortality is among newborns with infection acquired from their mothers (25%-50%). Mortality among those over 60 years of age is also high (10%-20%).…”
Section: Incidence Of Infectionmentioning
confidence: 99%
“…5 Countries with surveillance programs have reported rates of infection from 0.6 to 6.2 cases per million, with countries having active surveillance programs reporting the highest incidence. 5,[7][8][9][10][11] The case-fatality rates vary from country to country, but invariably the highest mortality is among newborns with infection acquired from their mothers (25%-50%). Mortality among those over 60 years of age is also high (10%-20%).…”
Section: Incidence Of Infectionmentioning
confidence: 99%
“…It infects humans through ingestion of contaminated foods and can cause noninvasive diseases (gastroenteritis) and/ or serious invasive systemic diseases [4]. Given the increase in the elderly population in both developing and developed countries and the changes in food habits toward ready-to-eat products the incidence of listeriosis is increasing worldwide [5]. At the same time, increased numbers of international travellers and of food exchanges between countries means that food safety is a major health priority.…”
Section: Introductionmentioning
confidence: 99%
“…Death occurs in 20%-30% of cases, making listeriosis a leading cause of food poisoning deaths in Europe and the United States (1). An increasing rate of listeriosis has been reported in several European countries (2). Our study focused on the large increase in the number of reported listeriosis cases in England and Wales during 2 months in separate years (April 2001 andMarch 2003).…”
Section: P Revention Of Listeriosis (Infection Caused Bymentioning
confidence: 99%